2022
DOI: 10.3389/fphar.2022.962763
|View full text |Cite
|
Sign up to set email alerts
|

Raman and fluorescence micro-spectroscopy applied for the monitoring of sunitinib-loaded porous silicon nanocontainers in cardiac cells

Abstract: Nanomaterials are a central pillar in modern medicine. They are thought to optimize drug delivery, enhance therapeutic efficacy, and reduce side-effects. To foster this technology, analytical methods are needed to validate not only the localization and distribution of these nanomaterials, but also their compatibility with cells, drugs, and drug release. In the present work, we assessed nanoparticles based on porous silicon (pSiNPs) loaded with the clinically used tyrosine kinase inhibitor sunitinib for their e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 72 publications
(94 reference statements)
0
2
0
1
Order By: Relevance
“…The usefulness of RI for single-cell analysis at the level of individual organelles has been proven in our previous papers [66][67][68][69]. Moreover, fluorescence staining confirmed the effectiveness of RI for individual structure visualization and correctness of Raman data interpretation [70][71][72][73][74][75]. Scheme S1 in the Supplementary Materials shows the simplified illustration of the RI experiment idea and the comparison of RI and fluorescence data for one cell chosen from our database.…”
Section: Resultssupporting
confidence: 64%
“…The usefulness of RI for single-cell analysis at the level of individual organelles has been proven in our previous papers [66][67][68][69]. Moreover, fluorescence staining confirmed the effectiveness of RI for individual structure visualization and correctness of Raman data interpretation [70][71][72][73][74][75]. Scheme S1 in the Supplementary Materials shows the simplified illustration of the RI experiment idea and the comparison of RI and fluorescence data for one cell chosen from our database.…”
Section: Resultssupporting
confidence: 64%
“…Second, we found that there are 11 and 8 TFs regulating the hub genes SKP1 and BAP1, respectively, using the NetworkAnalyst database. Finally, based on the DGIdb database, we found that histone deacetylase inhibitors, such as vorinostat [ 62 ], panobinostat [ 63 , 64 ], mTOR pathway inhibitor everolimus [ 65 ], apitolisib [ 66 , 67 ], tyrosine kinase inhibitor sunitinib [ 68 ] and poly (ADP-ribose) polymerase inhibitor olaparib [ 69 ] may target the BAP1 gene and promote neural recovery after SCI.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the distribution of tyrosine kinase inhibitors such as sorafenib and sunitinib was monitored in cells using Raman bands located at 1028 cm −1 and 1320/1570 cm −1 , respectively. 31,75 In SRS imaging study, Fu et al 40 used also the Raman bands of nilotinib, chloroquine, and GNF and GNF at 1300 cm, 1370, and 1600 cm −1 to display their distribution in the cells. Besides, the distribution of doxorubicin and squalene-doxorubicin in cancer cells was detected through several Raman bands in the fingerprint region.…”
Section: Label-free Distribution Of Lapatinib In Cells By Raman Spect...mentioning
confidence: 99%